Anode catalyst capable of being updated in situ in electrolytic bath as well as preparation method and application of anode catalyst
By renovating the nickel-iron-based nano-oxygen evolution catalyst in situ in the electrolytic cell, using the S-element doped NiFe-LDH nanosheet array grown on the nickel-based self-supporting support, the problem of difficult to achieve both activity and stability of the existing catalyst is solved, and an efficient and long-lived oxygen electrolytic reaction is achieved.
Patent Information
- Application Number
- CN202411722284.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-07
AI Technical Summary
The existing nickel-iron-based oxygen evolution materials are inefficient in the process of electrolyzing hydrogen production, and are difficult to achieve both activity and stability, resulting in a shortening of the catalyst life.
The NiFe-LDH nanosheet array S-NiFe-LDH grown on a nickel-based self-supported support is used as the anode catalyst, and the activity and stability of the catalyst are restored by the method of in-situ renewal in the electrolytic cell.
An efficient oxygen electrolysis (OER) reaction under alkaline conditions was achieved. The catalyst maintained more than 90% of the initial catalytic performance during the oxygen evolution process of 500 hours, and was able to recover in situ after damage, reducing the production and maintenance costs of the catalyst.
Smart Images

Figure CN119571374A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic nanomaterials, and in particular relates to an anode catalyst which can be renewed in situ in an electrolytic cell, and a preparation method and application thereof. Background Art
[0002] Anode catalysts, as the main energy-consuming end in hydrogen production by water electrolysis, are a key link in the future development of green hydrogen energy. Compared with commercial Ru catalysts with small reserves and high prices, nickel-iron-based catalysts are a powerful alternative to Ru-based catalysts due to their high stability and high activity. However, current studies on the OER performance of nickel-iron-based nanocatalysts have shown that active sites are prone to detachment or deactivation during the oxygen evolution process, resulting in a decrease in the stability of oxygen evolution and a reduction in the life of the catalyst. Therefore, it is urgent to design the oxygen evolution catalyst in a reasonable structure and phase to enhance stability while retaining the catalyst activity.
[0003] However, it is difficult to design the structure and physical phase of an oxygen evolution catalyst with high activity and high industrial-grade stability. It has high requirements for experimental design, and it is often impossible to achieve both in the preparation of materials and experimental conditions, which seriously affects the oxygen evolution performance and stability of the prepared catalyst. Therefore, how to optimize the preparation of nickel-iron-based catalysts and design a suitable physical phase structure to obtain an alkaline oxygen evolution catalyst with both high stability and high activity is a key issue in promoting hydrogen production by water electrolysis and reducing the cost of hydrogen production. Summary of the invention
[0004] In view of the technical problems that the existing nickel-iron-based oxygen evolution materials have low efficiency and cannot achieve both activity and stability to achieve industrial-grade electrolysis of water to produce hydrogen, the present invention provides an anode catalyst that can be updated in situ in an electrolyzer, and a preparation method and application thereof. After a long period of oxygen evolution, the active sites on the surface of the nickel-iron-based nano oxygen evolution catalyst of the present invention may fall off or become inactivated. The present invention also provides a technical solution for restoring the activity of the catalyst of the present invention and having high stability without further processing (such as disassembly) the electrolyzer.
[0005] In a first aspect, the present invention provides an anode catalyst that can be updated in situ in an electrolytic cell, wherein the anode catalyst that can be updated in situ in an electrolytic cell comprises: a nickel-based self-supporting carrier, and a NiFe-LDH nanosheet array S-NiFe-LDH composed of an alternating combination of S-doped nickel hydroxide and iron hydroxide supported on the nickel-based self-supporting carrier.
[0006] Preferably, in the anode catalyst, the mass ratio of Fe and Ni is 0.05-3:1, the doping amount of the S element accounts for 0.1-3% of the total mass of the catalyst, and the mass of the S-doped nanosheet array S-NiFe-LDH accounts for 1-15% of the total mass of the anode catalyst.
[0007] Preferably, the current density of the anode catalyst under alkaline conditions is 500 mA / cm 2 The initial overpotential of OER electrocatalysis is 200-420 mV, and it can be used at 300 mA / cm 2 The current density of alkaline oxygen evolution was maintained at more than 90% of the initial catalytic performance for 500h; After the anode catalyst is damaged in an alkaline environment, it can be restored in situ without disassembling the electrolytic cell. The restored catalyst has a current density of 500 mA / cm under alkaline conditions. 2 The ratio of the initial overpotential of OER electrocatalysis to the overpotential of the original catalyst is 1-1.3.
[0008] In a second aspect, the present invention provides a method for preparing the above-mentioned anode catalyst that can be renewed in situ in an electrolytic cell, the preparation method comprising the following steps: (1) mixing an oxidizing sulfur source and a reducing sulfur source to prepare a precursor solution containing a sulfur source; (2) placing a nickel-based self-supporting support into the above-mentioned precursor solution containing a sulfur source to allow the S element to undergo oxidative corrosion growth on the nickel-based self-supporting support, and obtaining an S-doped nickel hydroxide nanosheet array grown on the surface of the self-supporting support after washing and drying; (3) The S-doped nickel hydroxide nanosheet array grown on the surface of the self-supporting carrier is used as an anode and a carbon rod is used as a cathode, and a constant current treatment is performed in a solution containing an iron source to obtain the anode catalyst that can be updated in situ in the electrolytic cell.
[0009] Preferably, in step (1), the oxidizing sulfur source is at least one of potassium hydrogen sulfate, sodium pyrosulfate, sodium persulfate, and ammonium persulfate, and the reducing sulfur source is at least one of ammonium thiosulfate, sodium thiosulfate, sodium pyrosulfite, and sodium sulfide; The molar ratio of the oxidizing sulfur source to the reducing sulfur source is 1:0.1-1.
[0010] Preferably, in step (2), the nickel-based self-supporting carrier is a nickel mesh or nickel foam with a purity higher than 99.99%; 0.1-5 cm 2 The nickel-based self-supporting carrier is preferably 0.5 to 4 cm 2 .
[0011] Preferably, in step (2), the temperature of the oxidation corrosion growth is not higher than 50° C., and the time is 3-60 minutes.
[0012] Preferably, in step (3), the iron source is at least one of ammonium ferrous sulfate, ferrous sulfate, and ferrous ferrocyanide, preferably ammonium ferrous sulfate; the concentration of ferrous ions in the solution containing the iron source is 0.002-0.15 mol / L; The ratio of the iron source to the nickel-based self-supporting body is 1 cm 2 A 0.01-0.1 mol iron source was used.
[0013] Preferably, in step (3), the constant current treatment condition is a constant current of 1-30 mA / cm 2 Oxidation 1-60 minutes.
[0014] In a third aspect, the present invention provides an application of the above-mentioned anode catalyst that can be renewed in situ in an electrolyzer in producing hydrogen by electrolysis of water.
[0015] Beneficial Effects (1) The S-NiFe-LDH catalyst of the present invention can be rapidly scaled up for preparation and also reduces the overpotential during oxygen evolution, thereby achieving efficient OER reaction in alkaline electrolyte; (2) The present invention uses a "multi-step oxidation method" to prepare a nanosheet array on a nickel mesh, creating an air-repellent and hydrophilic structure, thereby reducing energy consumption; (3) Precious metals are relatively expensive. Adding precious metals to catalysts will increase costs, which is not conducive to actual production applications. The preparation method of the present invention does not use precious metals but selects easily available non-precious metal elements. The preparation conditions are mild and simple, which greatly reduces the cost of the catalyst and has high economic benefits and practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a SEM image of NiFeS prepared in Example 1; Figure 2 TEM photo (a), HRTEM photo (b) and selected area electron diffraction photo (c) of NiFeS prepared in Example 1; Figure 3 XRD pattern of NiFeS prepared in Example 1; Figure 4 This is the full XPS spectrum of NiFeS prepared in Example 1; Figure 5 This is a detailed spectrum of nickel in NiFeS prepared in Example 1; Figure 6The current density of NiFeS prepared in Example 1, NiFeS-2 prepared in Comparative Example 1, S-Ni(OH)2 / NM prepared in Comparative Example 2, NM prepared in Comparative Example 3, and NiFe-LDH / NM prepared in Comparative Example 4 are curves showing changes with voltage; Figure 7 The current density of NiFeS prepared in Example 1 changes with time at constant voltage; Figure 8 The SEM photo (a) of the NiFeS nanocatalyst prepared in Example 1, the SEM photo (b) of the D-NiFeS prepared in Example 2, and the SEM photo (c) of the R-NiFeS; Fig. 9 This is the XPS image of D-NiFeS prepared in Example 2; Fig.10 This is the XPS image of R-NiFeS prepared in Example 2; Fig.11 The current density of NiFeS prepared in Example 1 changes with time at a constant voltage in an electrolytic cell; Fig.12 The curves of the cell pressure in the electrolytic cell of NiFeS prepared in Example 1, D-NiFeS prepared in Example 2 and R-NiFeS prepared in Example 3 as a function of the current density; Fig.13 The curves of the cell pressure change over time in the electrolytic cell of NiFeS prepared in Example 1, D-NiFeS prepared in Example 2 and R-NiFeS prepared in Example 3; Fig.14 The SEM image of NiFeS-2 prepared in Comparative Example 1; Fig.15 This is the SEM image of S-Ni(OH)2 / NM prepared in Comparative Example 2; Fig.16 is the SEM image of NM prepared in Comparative Example 3; Fig.17 This is the SEM image of NiFe-LDH / NM prepared in Comparative Example 4. DETAILED DESCRIPTION
[0017] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0018] First, the present invention provides an anode catalyst S-NiFe-LDH nanocatalyst that can be renewed in situ in an electrolytic cell. The anode catalyst S-NiFe-LDH nanocatalyst that can be renewed in situ in an electrolytic cell comprises: a nickel-based self-supporting carrier, and a NiFe-LDH nanosheet array S-NiFe-LDH composed of an alternating combination of S-doped nickel hydroxide and iron hydroxide supported on the nickel-based self-supporting carrier.
[0019] In some embodiments, the NiFe-LDH nanosheets may be rectangular, and the size of the nanosheets may be 100-800 nm, preferably 300-600 nm. If the nanosheets are too large, the number of active sites per unit area will be reduced; if the nanosheets are too small, the nanosheets will be easily peeled off due to the peeling effect of the bubbles, thereby reducing the stability of the catalyst.
[0020] In some embodiments, the mass ratio of Fe and Ni in the anode catalyst may be 0.05-3: 1. Controlling the mass ratio of Fe and Ni within this range can ensure a high alkaline oxygen evolution activity of the catalyst.
[0021] In some embodiments, the doping amount of the S element may account for 0.1-3% of the total mass of the catalyst. Too high S doping will change the composition of the catalyst, while too low S doping will not be able to play a good catalytic role.
[0022] In some embodiments, the mass of the S-doped nanosheet array S-NiFe-LDH may account for 1-15% of the total mass of the anode catalyst.
[0023] The S-NiFe-LDH nanocatalyst of the present invention has a current density of 500 mA / cm under alkaline conditions. 2 The initial overpotential of OER electrocatalysis is 200-420 mV, and it can be used at 300 mA / cm 2 The current density of alkaline oxygen evolution was 500h without significant catalytic performance attenuation (maintaining more than 90% of the initial catalytic performance). After the S-NiFe-LDH nanocatalyst of the present invention is damaged in an alkaline environment, it can be restored in situ without disassembling the electrolytic cell. The restored catalyst has a current density of 500mA / cm 2 The ratio of the initial overpotential of OER electrocatalysis to the overpotential of the original catalyst is 1-1.3.
[0024] The following is an exemplary description of the method for preparing the anode catalyst that can be renewed in situ in the electrolytic cell provided by the present invention. The preparation method may include the following steps: (1) mixing an oxidizing sulfur source and a reducing sulfur source to prepare a precursor solution containing a sulfur source; (2) placing a nickel-based self-supporting support into the above-mentioned precursor solution containing a sulfur source to allow the S element to undergo oxidative corrosion growth on the nickel-based self-supporting support, and obtaining an S-doped nickel hydroxide nanosheet array grown on the surface of the self-supporting support after washing and drying; (3) The S-doped nickel hydroxide nanosheet array grown on the surface of the self-supporting carrier is used as an anode and a carbon rod is used as a cathode, and a constant current treatment is performed in a solution containing an iron source to obtain the anode catalyst that can be updated in situ in the electrolytic cell.
[0025] In some embodiments, in step (1), the valence state of part of the sulfur in the oxidizing sulfur source is hexavalent, which can be at least one of potassium hydrogen sulfate (KHSO5), sodium pyrosulfate (Na2S2O7), sodium persulfate (Na2S2O8), and ammonium persulfate; the valence state of part of the sulfur in the reducing sulfur source is negative divalent, which can be at least one of ammonium thiosulfate, sodium thiosulfate, sodium pyrosulfite (Na2S2O5), and sodium sulfide (Na2S).
[0026] In some embodiments, in step (1), the molar ratio of the oxidizing sulfur source to the reducing sulfur source may be 1:0.1-1.
[0027] The oxidizing sulfur source can provide an oxidizing environment for subsequent corrosion of the surface of the nickel-based self-supporting carrier, thereby promoting the formation of the nanosheet array; the reducing sulfur source is an initiator, which promotes the redox reaction. By controlling the molar ratio of the oxidizing and reducing sulfur sources within the above-mentioned suitable range, the size of the nanosheet array can be controlled, which is conducive to the manufacture of an air-repellent and hydrophilic structure.
[0028] In some embodiments, in step (1), the solvent of the precursor solution can be one of methanol, ethanol, and deionized water, preferably deionized water.
[0029] In some embodiments, in step (1), the ratio of the oxidizing sulfur source to the solvent may be 3-100 mL of solvent per 1 mmol of the oxidizing sulfur source, preferably 5-20 mL.
[0030] As an example, during the preparation of the precursor solution containing the sulfur source, the solution can be uniformly mixed by ultrasound and stirring. For example, the solution is ultrasounded for 3-10 minutes and stirred at 0-25° C. for 1-40 minutes to be uniformly mixed.
[0031] In some embodiments, in step (2), the nickel-based self-supporting carrier may be a nickel mesh or nickel foam with a purity higher than 99.99%.
[0032] In some embodiments, in step (2), 0.1-5 cm 2 The nickel-based self-supporting carrier is preferably 0.5 to 4 cm 2 .
[0033] In some embodiments, in step (2), the temperature of the oxidation corrosion growth may be no higher than 50°C, and the time may be 3-60 minutes. If the temperature is too high, the reaction is too violent, which is not conducive to the formation of nanosheets; if the time is too long, the nanosheets will grow excessively, affecting the conductivity of the substrate.
[0034] In some embodiments, in step (2), the drying temperature may be 20 to 80°C.
[0035] In some embodiments, in step (3), the iron source can be at least one of ammonium ferrous sulfate, ferrous sulfate, and ferrous ferrocyanide, preferably ammonium ferrous sulfate; the solvent in the solution containing the iron source can be at least one of methanol, ethanol, and water.
[0036] In some embodiments, in step (3), the concentration of ferrous ions in the solution containing the iron source may be 0.002-0.15 mol / L; the ratio of the iron source to the nickel-based self-supporting body may be 1 cm 2 A 0.01-0.1 mol iron source was used.
[0037] In some embodiments, in step (3), the constant current treatment condition can be a constant current of 1-30 mA / cm 2 Oxidation 1-60 minutes.
[0038] Among them, if the concentration of ferrous ions is too low or too high, the ratio of nickel to iron will be unbalanced, resulting in a decrease in oxygen evolution performance; if the current density is too high or the time is too long, burning is likely to occur; if the current density is too low or the time is not enough, it is difficult for iron to be completely introduced into the nanosheets to form NiFe-LDH.
[0039] The electrochemical oxidation treatment adopted by the present invention is non-toxic and harmless, and does not produce harmful and toxic liquids. Through wet chemical oxidation treatment, while introducing iron elements to form NiFe-LDH, low-valent sulfur is excluded, so that S is no longer generated in the OER process, reducing the Faraday efficiency.
[0040] In the anode catalyst provided by the present invention, the S element plays a role in reducing the overpotential of oxygen evolution. After a period of oxygen evolution, most of the S will be precipitated. When the performance of the catalyst decreases, it can be updated in situ in the electrolytic cell to eventually restore its original performance. In this method, without disassembling the electrolytic cell, first a sulfur source solution is used to re-corrode and oxidize to form new nanosheets, and then an iron source solution is used for electrochemical oxidation to form S-doped NiFe-LDH. The nanosheets prepared in situ by the present invention without disassembling the electrolytic cell are still rectangular nanosheets, and iron is reintroduced into the nanosheets.
[0041] The S-NiFe-LDH nanocatalyst of the present invention can be resynthesized in situ in the electrolytic cell after the performance is reduced. Since the oxygen evolution catalyst will produce active site shedding and deactivation during the long-term oxygen evolution process, resulting in the reduction of catalyst carrier performance, and the cost of replacing the catalyst in the electrolytic cell is high and the benefit is low. Therefore, the present invention can achieve the in-situ resynthesis of the S-NiFe-LDH nanocatalyst in the electrolytic cell by optimizing the synthesis steps of the catalyst: the wet chemical oxidation method realizes the construction of the nanosheet array through the sulfur-containing solution; the electrochemical oxidation method forms NiFe-LDH by constant current oxidation in a ferrous ion solution.
[0042] As an example preparation scheme of S-NiFe-LDH nanocatalyst, the following steps may be included: (1) Add 1 mmol of ammonium persulfate to 35-100 mL of deionized water at room temperature; (2) magnetically stirring the solution obtained in step (1) at room temperature for 0.1 to 1 h to obtain a uniform mixed solution; (3) adding 0.1-1 mmol sodium thiosulfate to the mixed solution prepared in step (2) and placing a nickel-based self-supporting carrier, keeping the mixture at 0-50° C. for 0.1-1 h, taking it out, washing and drying it to obtain an S-Ni(OH)2 precursor (an array of S-doped nickel hydroxide nanosheets grown on the surface of the self-supporting carrier); (4) The precursor obtained in step (3) is used as an anode in a 1-50 mmol / L ammonium ferrous sulfate solution at 3-20 mA / cm 2 The S-NiFe-LDH nanocatalyst was obtained by oxidation treatment at a constant current density of 0.1 to 1 hour.
[0043] The S-NiFe-LDH nanocatalyst of the present invention presents an orderly arranged nanosheet morphology as a whole. The S-NiFe-LDH nanocatalyst can have high activity and high stability at the same time in alkaline conditions, and the catalytic performance has not decreased for a long time during the IT test. In addition, the catalyst of the present invention can be updated in situ without disassembling the electrolyzer, restoring the catalyst's efficient and stable alkaline oxygen evolution performance. This is of great significance for solving the urgent need to reduce energy consumption in the current alkaline water electrolysis hydrogen production and provide an oxygen evolution catalyst with high stability and high activity. The use of the anode catalyst that can be updated in situ in the electrolyzer provided by the present invention in the production of hydrogen by water electrolysis at all pH values, especially alkaline.
[0044] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.
[0045] Unless otherwise specified: In the single-cell test, the electrocatalytic activity was tested by the three-electrode method using a Shanghai Chenhua CHI 760E electrochemical workstation. The reference electrode was an Ag / AgCl electrode and the counter electrode was a carbon rod. The electrocatalytic activity test was carried out in an alkaline environment in a 1M KOH aqueous solution by electrolyzing water to produce oxygen. The test in the electrolyzer was carried out in a 30%wt KOH aqueous solution by electrolyzing water to produce oxygen, and the counter electrode was a homemade NiMo4 loaded on nickel foam.
[0046] Example 1
[0047] The preparation method of the anode catalyst that can be renewed in situ in the electrolytic cell provided in this comparative example comprises the following steps: adding 4.4 mmol of ammonium persulfate to 80 mL of deionized water at room temperature and stirring for 10 min, adding 3.2 mmol of sodium thiosulfate and stirring at 5°C for 2 minutes, and then placing 10 cm 2 A 46-mesh nickel mesh was prepared and kept warm for 10 minutes to obtain a nickel mesh with S-Ni(OH)2 nanosheets uniformly grown on the surface, which was then washed with deionized water and dried to obtain a precursor; The precursor was used as an anode in a 0.01 mol / L ammonium ferrous sulfate solution at 10 mA / cm 2The self-supporting body was then taken out, washed with water, and dried in vacuo to obtain a sulfur-doped NiFe-LDH nanosheet nanocatalyst (denoted as NiFeS).
[0048] Example 2
[0049] According to the process flow in Example 1, a NiFeS nanocatalyst material was obtained. The material was placed under an overpotential of 0.88 V (vsHg / HgO) for oxygen evolution for 24 h. The performance of the NiFeS nanocatalyst decreased rapidly (recorded as D-NiFeS at this time). The same preparation method as Example 1 was used, except that the nickel mesh was replaced with D-NiFeS. After this step, the catalyst performance was restored (recorded as R-NiFeS).
[0050] Example 3
[0051] D-NiFeS was obtained according to the process flow in Example 2, and the D-NiFeS catalyst was subsequently restored to the R-NiFeS catalyst process at 2*2 cm 2 The process is carried out in an electrolytic cell of a certain area.
[0052] Comparative Example 1
[0053] Referring to the process flow of Example 1, only the electrochemical oxidation time was increased to 70 min, and the prepared material was recorded as NiFeS-2.
[0054] Electrochemical oxidation for too long will lead to the excessive introduction of iron elements into the nanosheets, which will reduce the catalyst's activity for oxygen evolution in water electrolysis.
[0055] Comparative Example 2
[0056] Referring to the process flow of Example 1, but without performing electrochemical oxidation, the prepared material is recorded as S-Ni(OH)2 / NM.
[0057] Comparative Example 3
[0058] The nickel mesh without any treatment is denoted as NM.
[0059] Comparative Example 4
[0060] Ni(NO3)2·6H2O (0.99 mmol), Fe(NO3)3·9H2O (0.33 mmol), NH4F (5 mmol) and urea (5 mmol) were dissolved in 20 mL of deionized water and ultrasonically treated for 30 min. The resulting solution was then transferred to a 30 mL Teflon autoclave and the pre-treated 2*3 cm 2 The nickel mesh was placed into the solution and subjected to a hydrothermal reaction at 120 °C for 12 h to obtain NiFe-LDH / NM.
[0061] Figure 1 This is the SEM image of NiFeS prepared in Example 1.
[0062] Figure 2 The TEM photo (a), HRTEM photo (b) and selected area electron diffraction photo (c) of NiFeS prepared in Example 1. According to HRTEM, it can be distinguished that the interior of the nanosheet in photo (a) is composed of nickel-iron hydroxide.
[0063] Figure 3 This is the XRD pattern of NiFeS prepared in Example 1. It can be seen from the figure that the main crystal phases are nickel metal and NiFe-LDH, and the diffraction peak of Ni in the figure mainly comes from the nickel mesh.
[0064] Figure 4 This is the full XPS spectrum of NiFeS prepared in Example 1. As can be seen from the figure, the main elements are Ni, Fe and S.
[0065] Figure 5 This is a detailed spectrum of nickel in NiFeS prepared in Example 1. It can be seen from the figure that the nickel on the catalyst surface exists not only as nickel metal in the nickel mesh, but also as a divalent nickel compound.
[0066] Figure 6 The current density of NiFeS prepared in Example 1, NiFeS-2 prepared in Comparative Example 1, S-Ni(OH)2 / NM prepared in Comparative Example 2, NM prepared in Comparative Example 3, and NiFe-LDH / NM prepared in Comparative Example 4 are plotted against voltage. It can be seen from the figure that the current density of NiFeS nanocatalyst under alkaline conditions is 500 mA / cm 2 The overpotential of OER electrocatalysis is 370 mV, which shows good OER electrocatalytic activity. The current density of NiFeS-2 nanocatalyst is 500 mA / cm under alkaline conditions. 2 The overpotential of OER electrocatalysis is 490 mV. The OER electrocatalytic activity of NiFeS-2 prepared in Comparative Example 1 is significantly worse than that of NiFeS prepared in Example 1. This is because the electrochemical oxidation time is too long and the nanosheet structure on the catalyst surface is destroyed. The current density of S-Ni(OH)2 / NM nanocatalyst under alkaline conditions is 500 mA / cm 2 The overpotential of OER electrocatalysis is 510 mV. The OER electrocatalytic activity of S-Ni(OH)2 / NM prepared in Comparative Example 2 is significantly worse than that of NiFeS prepared in Example 1. This is because the nanosheets are not converted into NiFe-LDH without electrochemical oxidation. The current density of NM nanocatalyst under alkaline conditions is 500 mA / cm 2The overpotential of OER electrocatalysis is 500 mV. The OER electrocatalytic activity of NM prepared in Comparative Example 3 is significantly worse than that of NiFeS prepared in Example 1. This is because no wet chemical oxidation is performed, no Ni(OH)2 nanosheets are generated on the surface of the nickel mesh, and no sulfur element is introduced, so NiFe-LDH cannot be formed during electrochemical oxidation.
[0067] Figure 7 This is a graph showing the change of current density over time at constant voltage for NiFeS prepared in Example 1. As can be seen from the figure, its performance did not show a significant decrease during the 1500h oxygen evolution process.
[0068] Figure 8 The SEM photo (a) of the NiFeS nanocatalyst prepared in Example 1, the SEM photo (b) of the D-NiFeS prepared in Example 2, and the SEM photo (c) of the R-NiFeS prepared in Example 2. As can be seen from the figure, there are no obvious nanosheets on the surface of the SEM photo (b) of the D-NiFeS prepared in Example 2, but nanosheets reappear on the surface of the R-NiFeS.
[0069] Fig. 9 This is the XPS graph of D-NiFeS prepared in Example 2. As can be seen from the graph, it contains elements such as Ni and Fe.
[0070] Fig.10 This is the XPS graph of R-NiFeS prepared in Example 2. As can be seen from the graph, it contains elements Ni, Fe, S, etc.
[0071] Fig.11 This is the curve of the current density changing with time under constant voltage in the electrolytic cell of NiFeS prepared in Example 1. It can be seen from the figure that the catalyst performance has not been significantly attenuated.
[0072] Fig.12 The curves of the cell voltage in the electrolytic cell versus the current density are shown for NiFeS prepared in Example 1, D-NiFeS prepared in Example 2, and R-NiFeS prepared in Example 3. As can be seen from the figure, the performance of R-NiFeS is close to that of NiFeS.
[0073] Fig.13 The curves of the cell pressure change over time in the electrolytic cell of NiFeS prepared in Example 1, D-NiFeS prepared in Example 2, and R-NiFeS prepared in Example 3. It can be clearly observed that the performance of the D-NiFeS catalyst is significantly improved after it is restored to the R-NiFeS catalyst.
[0074] Fig.14 This is a SEM image of NiFeS-2 prepared in Comparative Example 1. As can be seen from the image, a large number of nanosheets of different sizes appear on the surface and the average size is greater than 1 micron.
[0075] Fig.15 This is the SEM image of S-Ni(OH)2 / NM prepared in Comparative Example 2. As can be seen from the figure, there are evenly distributed nanosheets on the surface of the nickel mesh.
[0076] Fig.16 This is a SEM image of the NM prepared in Comparative Example 3. The image shows that there are no nanosheets on the surface of the nickel mesh.
[0077] Fig.17 This is a SEM image of NiFe-LDH / NM prepared in Comparative Example 4. The image shows that the surface of the nickel mesh is evenly covered with nanosheets.
[0078] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. An anode catalyst that can be renewed in situ in an electrolytic cell, characterized in that: The anode catalyst that can be renewed in situ in the electrolytic cell includes: a nickel-based self-supporting carrier, and a NiFe-LDH nanosheet array S-NiFe-LDH composed of an alternating combination of S-doped nickel hydroxide and iron hydroxide supported on the nickel-based self-supporting carrier.
2. The anode catalyst that can be renewed in situ in the electrolytic cell according to claim 1, characterized in that: In the anode catalyst, the mass ratio of Fe and Ni is 0.05-3:1, the doping amount of the S element accounts for 0.1-3% of the total mass of the catalyst, and the mass of the S-doped nanosheet array S-NiFe-LDH accounts for 1-15% of the total mass of the anode catalyst.
3. The anode catalyst that can be renewed in situ in the electrolytic cell according to claim 1 or 2, characterized in that: The current density of the anode catalyst under alkaline conditions is 500 mA / cm 2 The initial overpotential of OER electrocatalysis is 200-420 mV, and it can be used at 300 mA / cm 2 The current density of alkaline oxygen evolution was maintained at more than 90% of the initial catalytic performance for 500h; After the anode catalyst is damaged in an alkaline environment, it can be restored in situ without disassembling the electrolytic cell. The restored catalyst has a current density of 500 mA / cm under alkaline conditions. 2 The ratio of the initial overpotential of OER electrocatalysis to the overpotential of the original catalyst is 1-1.
3.
4. A method for preparing an anode catalyst that can be renewed in situ in an electrolytic cell according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing an oxidizing sulfur source and a reducing sulfur source to prepare a precursor solution containing a sulfur source; (2) placing a nickel-based self-supporting support into the above-mentioned precursor solution containing a sulfur source to allow the S element to undergo oxidative corrosion growth on the nickel-based self-supporting support, and obtaining an S-doped nickel hydroxide nanosheet array grown on the surface of the self-supporting support after washing and drying; (3) The S-doped nickel hydroxide nanosheet array grown on the surface of the self-supporting carrier is used as an anode and a carbon rod is used as a cathode, and a constant current treatment is performed in a solution containing an iron source to obtain the anode catalyst that can be updated in situ in the electrolytic cell.
5. The preparation method according to claim 4, characterized in that: In step (1), the oxidizing sulfur source is at least one of potassium hydrogen sulfate, sodium pyrosulfate, sodium persulfate, and ammonium persulfate, and the reducing sulfur source is at least one of ammonium thiosulfate, sodium thiosulfate, sodium pyrosulfite, and sodium sulfide; The molar ratio of the oxidizing sulfur source to the reducing sulfur source is 1:0.1-1.
6. The preparation method according to claim 4 or 5, characterized in that: In step (2), the nickel-based self-supporting carrier is a nickel mesh or nickel foam with a purity higher than 99.99%; Use 0.1-5 cm 2 The nickel-based self-supporting carrier is preferably 0.5 to 4 cm 2 .
7. The preparation method according to any one of claims 4 to 6, characterized in that: In step (2), the temperature of the oxidation corrosion growth is not higher than 50° C., and the time is 3-60 minutes.
8. The preparation method according to any one of claims 4 to 7, characterized in that: In step (3), the iron source is at least one of ammonium ferrous sulfate, ferrous sulfate, and ferrous ferrocyanide, preferably ammonium ferrous sulfate; the concentration of ferrous ions in the solution containing the iron source is 0.002-0.15 mol / L; The ratio of the iron source to the nickel-based self-supporting body is 1 cm 2 A 0.01-0.1 mol iron source was used.
9. The preparation method according to any one of claims 4 to 8, characterized in that: In step (3), the constant current treatment condition is a constant current of 1-30 mA / cm 2 Oxidation 1-60 minutes.
10. Use of an anode catalyst capable of being renewed in situ in an electrolyzer according to any one of claims 1 to 3 in producing hydrogen by electrolysis of water.
Citation Information
Cited By
Nickel sulfide self-supporting water electrolysis electrode in-situ construction method adapting to fluctuating working conditions
CN122105462A